The Effect of The Covid-19 Pandemic on MSMES In Yogyakarta City - Adhisena, Muhammad; Wiranatakusuma, Dimas Bagus; Kamil, Muhamad (Universitas Muhammadiyah Yogyakarta, 2023)
MSMEs are Micro, Small and Medium Enterprises that are usually carried out by the community to help their economy, not only that MSMEs also help the country's economy at the same time. However, currently MSMEs are in trouble because they are affected by Covid 19, so that it has an impact on the country's economy. This research uses a qualitative method, namely by conducting interviews with MSME actors. From the results obtained, it will provide answers about the impact of Covid 19 from each different MSME actor, because the impact of each seller will be different.